Towards a Standardization Of Personal Names: The Case of the Ethnic Chinese in Singapore - Peter KW Tan (Names, 2006)
Abstract The evolution of personal names in western Europe can be said to be characterized by the phenomenon of standardization (Wilson 1998). This article seeks to examine whether this general rubric is of use in the context of hybridized names, specifically the names of the ethnic Chinese in Singapore. I examine names obtained from a school year book in Singapore against the backdrop of the traditional pattern as documented by Jones (1997). Notable changes include the increased use of English-based given names and the way Chinese given names are represented: the tendency is towards having them based on Mandarin Chinese as opposed to other varieties of Chinese, and of having them spelt in a standard way of sorts. This is in line with the government's preferences and supports the standardization thesis. There is, however, strong resistance to the standardization of Chinese surnames.